A Water‐Based Chitosan–Maleimide Precursor for Bioconjugation: An Example of a Rapid Pathway for an In Situ Injectable Adhesive Gel. Issue 19 (27th July 2016) - Matsumoto, Masahiro; Udomsinprasert, Wanvisa; Laengee, Prayoon; Honsawek, Sittisak; Patarakul, Kanitha; Chirachanchai, Suwabun
Abstract : Chitosan conjugated with maleimide (CS–Mal) as a potential precursor for bioconjugation and the example of the application in in situ injectable adhesive gel is proposed. The homogeneous reaction in water/dimethyl sulfoxide (DMSO) (1:1) followed by dialysis in HCl (10 × 10 −3 m ) is a good condition to obtain CS–Mal. When SH–PEG–SH is applied as the crosslinker, the gel can be obtained in a few seconds without any by‐products at room temperature. The gel formation and properties are controllable by simply varying the concentration and the molecular weight of CS, the Mal substitution degree, and the temperature. The gel is injectable and shows adhesive property for soft tissue. Moreover, the gel shows not only biocompatibility to SAOS2 cells but also antimicrobial activity against both gram‐negative and gram‐positive bacteria. CS–Mal is useful not only for bioconjugation of CS but also for development of biomaterials. Abstract : Chitosan conjugated with maleimide is proposed as a potential precursor for bioconjugation and application for in situ injectable adhesive gel. When SH–PEG–SH is applied as the crosslinker, the gel can be obtained in a few seconds without any by‐products at room temperature. The gel is not only injectable but also shows biocompatibility, adhesion properties, and antimicrobial activities.